2002
DOI: 10.1192/bjp.181.6.488
|View full text |Cite
|
Sign up to set email alerts
|

Stigma and expressed emotion: a study of people with schizophrenia and their family members in China

Abstract: Clinicians should assess the effect of stigma as part of the standard work-up for patients with mental illness, and help patients and family members reduce the effect of stigma on their lives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
161
4
5

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 227 publications
(186 citation statements)
references
References 17 publications
15
161
4
5
Order By: Relevance
“…The first and fourth factors (intrusiveness and degree of carer's emotional involvement) in the Chinese version highlight the fact that a schizophrenic patient perceives a family with high EE as being highly intrusive to his/her daily activities and private affairs, and, in addition, the family might be seen to indulge in excessive emotional displays and negative preoccupations as well as statements of attitude towards the patient. This perception is consistent with the Chinese belief that open expression of emotions, either positive or negative, should be discouraged and the cultural emphasis on self and emotional control (Phillips et al, 2002;Yeo and Meiser, 2003). It can be argued that Chinese people believe that excessive emotion is harmful to an individual's physical and mental health and that a person should keep his/her emotions under control to maintain family functioning and relationships.…”
Section: Discussionsupporting
confidence: 80%
“…The first and fourth factors (intrusiveness and degree of carer's emotional involvement) in the Chinese version highlight the fact that a schizophrenic patient perceives a family with high EE as being highly intrusive to his/her daily activities and private affairs, and, in addition, the family might be seen to indulge in excessive emotional displays and negative preoccupations as well as statements of attitude towards the patient. This perception is consistent with the Chinese belief that open expression of emotions, either positive or negative, should be discouraged and the cultural emphasis on self and emotional control (Phillips et al, 2002;Yeo and Meiser, 2003). It can be argued that Chinese people believe that excessive emotion is harmful to an individual's physical and mental health and that a person should keep his/her emotions under control to maintain family functioning and relationships.…”
Section: Discussionsupporting
confidence: 80%
“…When compared to Ng and Sun's [35] [14] studies that over 40% of family members of patients with schizophrenia were rated as having high EE.…”
Section: Levels Of Perceived Ee In Chinese Patients With Smimentioning
confidence: 72%
“…For example, in India, emotional involvement is the norm and if a carer does not show much emotional involvement, it is seen as lack of care for the ill relative [13]. In Chinese population, Li and Arthur [12] and Philips et al [14] found that over 40% of Chinese family members of patients with schizophrenia were rated as showing high EE. They also observed that there was a significant increase in the relative risk of illness relapse for the Chinese patients with high EE, when compared to those in low EE families.…”
Section: Introductionmentioning
confidence: 99%
“…stigma) with respect to seeking professional care than urban residents. In contrast, Phillips et al (2002) found that people with schizophrenia living in more urbanized areas of China report a greater influence of stigma in their lives; they feel socially inferior because of their difficulty meeting the minimal adult standards expected of city dwellers. Because stigma can discourage the use of psychiatric care (e.g.…”
Section: Introductionmentioning
confidence: 89%